Efektivitas Permainan Balok Membangun dalam Meningkatkan Perilaku Prososial Anak Usia Dini - Tsabith, Naraya Tsabith; Masnipal, Masnipal; Taja, Nadri (UNISBA Press, 2025)
Abstract. Prosocial behavior such as being willing to share, enjoying helping, and playing together with friends is very important for learning to make friends and socialize at a young age. In order for kids to be able to make friends and socialize well in their surroundings, this skill needs to be taught from a young age.. Kindergarten, as the first official learning place for children, has a significant part in helping the development of this ability from the beginning.. Building block play can encourage prosocial behavior. Playing with blocks not only trains children's motor skills and thinking, but also fosters the spirit of cooperation, storytelling, and helping friends to complete the game together.. Through block play, children learn to patiently wait for their turn and begin to understand the importance of valuing their friends' ideas.. This research aims to determine how effective building block play are in increasing prosocial behavior in kids between the ages of five and six in kindergarten in Andir District. The research method used is quantitative research with a population consisted of 14 kindergarten schools and 32 respondents using total sampling method. The data analysis method used descriptive statistics by calculating the answers for each item in the questionnaire, processed using the Weighted Means Score formula (WMS). The research results show that building block play is very effective in improving prosocial behavior in early childhood in kindergarten, particulary in Andir District, with a score of 3,30 out of a total score of four. Abstrak. Perilaku prososial seperti mau berbagi, suka menolong, dan bermain bersama teman – teman sangat penting untuk belajar berteman dan bersosialisasi sejak anak masih kecil. Supaya anak bisa berteman dan bergaul dengan baik di sekitarnya, kemampuan ini perlu diajarkan sejak anak masih kecil. Taman kanak – kanak, sebagai tempat belajar pertama yang resmi untuk anak, punya peran penting dalam membantu tumbuhnya kemampuan ini sejak awal. Permainan balok membangun dapat mendorong perilaku prososial. Kegiatan bermain balok tidak hanya melatih gerak dan cara berpikir anak, tetapi juga menumbuhkan semangat bekerja sama, saling bercerita, dan membantu teman untuk menyelesaikan permainan bersama. Melalui permainan balok, anak belajar sabar menanti giliran dan mulai memahami pentingnya menghargai ide teman. Studi ini bertujuan untuk mengetahui seberapa efektif permainan balok membangun dalam meningkatkan perilaku prososial anak usia 5 – 6 tahun di Taman Kanak – kanak di Kecamatan Andir. Metode penelitian yang digunakan yaitu metode kuantitatif dengan populasi penelitian sebanyak 14 sekolah TK serta 32 jumlah responden dengan metode total sampling. Metode analisis data menggunakan statistik deskriptif dengan menghitung jawaban untuk setiap item dalam angket dan diolah dengan menggunakan rumus Weighted Means Score (WMS). Hasil studi menunjukkan jika permainan balok membangun sangat efektif dalam meningkatkan perilaku prososial anak usia dini di Taman Kanak – kanak khususnya di Kecamatan Andir dengan perolehan skor sebesar 3,30 dalam total skor skala empat.